Ekspresi Seni Orang Miskin Sebagai Kebutuhan Integratif - Rohidi MA, Prof. Dr. Tjetjep Rohendi (Jurnal Budaya Nusantara, 2015)
Human need to express the feeling of beauty seem to apply universally and last long time.